Membangun Aplikasi Sistem Informasi Komunitas Motor Berbasis Android (Studi Kasus : GSX Community Boyolali-Klaten) - Fairus Yuliagustin; Saiful Bahri; Dwi Kristiani (JITU : Journal Informatic Technology And Communication, 2020)
Research titled utilization of android application to support the Information System and Registration of new members of the GSX community who are secretariat in Boyolali-Semarang Street Dusun I, Winong, Boyolali, Boyolali. The research began from March 18, 2019 until June 18, 2019, with the aim of a) Building an Android-based application in accordance with the problems that have been analyzed, b) Designing an Android-based application program that can help facilitate prospective members who wish to register GSX Community Boyolali-Klaten members, c) Creating an android-based application so that members can more easily access and find the latest information about the community. The research methodology used is the PIECES Method, object modeling using UML. The results achieved are an android application to facilitate the registration of new members and providing information.